Design and analysis of a deployable tetrahedron-based mobile robot constructed by Sarrus linkages. (October 2020) - Liu, Ran; Yao, Yan-an; Li, Yezhuo
Highlights: A deployable tetrahedron-based mobile robot is constructed by coupled Sarrus linkages. Two non-impact rolling gaits are designed based on the kinematics of the robot. The continuous non-impact rolling locomotion is planned to enable the robot reach arbitrary target. Two folding modes are developed according to its structure characteristics. Experiments on prototype validate the folding capability and locomotion performance of the robot. Abstract: In this paper, a novel deployable tetrahedron-based mobile robot constructed by Sarrus linkages with eight degrees of freedom (DOFs) is proposed. The robot is composed of a core tetrahedron and four branch tetrahedrons with a total of eight nodes and 18 planar RRR chains (R denotes revolute joint), and each node and any two branch chains connected to it is a Sarrus linkage. Referring to the kinematics of the general-type Sarrus linkage, the kinematics of the robot is analyzed in detail. Based on it, two non-impact rolling gaits of rolling in Direction I/II and rolling in Direction III are discussed, then the continuous non-impact rolling locomotion is elaborated. Besides, two folding modes of folding as an umbrella shape and deploying in radially reciprocating motion are developed. Finally, a prototype is manufactured, the rolling experiments indicate that the robot can roll in any direction for arbitrary distance with the trajectory of a series of triangles, and the two additional folding modes increase the convenience of storage and transportation of the robot.